INFORMATION SHARING BETWEEN WAQF BENEFICIARIES AND DONORS VIA A DIGITAL PLATFORM IN INSTILLING SOCIAL INNOVATION FROM THE PERSPECTIVE OF ISLAMIC ECONOMICS - Johari, Fuadah; Misbah, Hanim; Nor, Fauzias Mat; Haron, Hasnah; Ahmad, Azuan; Salim, Kinan; Ali, Ahmad Fahme (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
There is a significant information sharing and implementation gap in waqf research. The gap is in the availability of information sharing about the methods used by state agencies to centralise or share information, particularly regarding state-provided online services. Current waqf information in Malaysia is primarily in the stage of experience information sharing. The study is qualitative in nature from the Islamic Economic perspective. Thus, this study aims to investigate the acceptance of sharing information among Beneficiaries and Donors with the idea of using more, donating more and sharing more. This study then explores the application of the sharing information approach among Beneficiaries, Donors and Mutawalli. Focus Group Discussion (FGD) was held in three sessions for three different groups; 27 informants participated in this study with 15 males and 12 females, 11 states, various professions from government, private, retiree and others, with various ages from above 15 – 64 years old. The end of this study shows that all informants accept the interaction between Beneficiaries and Donors using the characteristic of 'using more, donating more, and sharing more'. Most informants felt that sharing information through social media using digital marketing effectively spreads information about Waqf to the public. Sharing information focusing on waqf promotion is crucial to make the public aware of Waqf products nationwide. Celebrity marketing, mosque activities, roadshows, TV and radio programmes, and word-of-mouth are popular approaches the informants have mentioned, in addition to digital marketing. A digital platform is one of the most critical tools for facilitating information sharing. As a result, suggested implications for sharing information at the first stage must continue to the second stage, which requires infrastructure support to increase the information sharing, which can tap into a broader segment of the public.